Ecohealth research in Southeast Asia: Past, present and the way forward - Hung Nguyen-Viet; Doria, S.; Dinh Xuan Tung; Mallee, H.; Wilcox, B.A.; Grace, Delia (Springer, 2015)
Ecohealth is a comprehensive approach to understanding health at its human, animal and environmental interface in a socio-ecological systems context. This approach was introduced widely in Southeast Asia (SEA) by the Canadian International Development Research Centre (IDRC) in the late 2000s. Aimed at addressing the problem of emerging infectious diseases (EIDs), numerous such projects and activities have been generated throughout the region. Ecohealth is increasingly converging with the One Health approach, as both movements emphasise a holistic understanding to health. We conducted a scoping review by considering all of the Ecohealth programmes, initiatives and projects that have been implemented in SEA since the introduction of the approach, and also gathered information from peer-reviewed literature. The objective of this paper is to review Ecohealth activities within SEA over the last 10 years to address the lessons learned, challenges faced and the way forward for Ecohealth in the region. Activities range from those focusing purely on capacity, projects focusing on research and projects covering both. Achievements to date include, for example, research contributing to the field of infectious diseases in relation to social ecological factors and associated urbanisation and agricultural intensification. Challenges remain at the project design and implementation level, in the available capacity and coordination to develop Ecohealth research teams in the countries, gauging teams’ assimilation of Ecohealth’s underlying tenets and their translation into sustainable disease prevention and control, as well as in the ability to scale up Ecohealth projects. We suggest that the way forward for Ecohealth should be from a regional perspective in terms of research, training and policy translation using Ecohealth in combination with the One Health approach.